An electrochemical sensor based on Fe3O4@PANI nanocomposites for sensitive detection of Pb2+ and Cd2+. Issue 39 (25th September 2018) - Kong, Ying; Wu, Tingting; Wu, Di; Zhang, Yong; Wang, Yaoguang; Du, Bin; Wei, Qin
Abstract : In this study, an easy-to-use electrochemical sensor was developed for the quantitative detection of lead ions (Pb 2+ ) and cadmium ions (Cd 2+ ). Abstract : In this study, an easy-to-use electrochemical sensor was developed for the quantitative detection of lead ions (Pb 2+ ) and cadmium ions (Cd 2+ ). Core-shell ferroferric oxide@polyaniline (Fe3 O4 @PANI) nanoparticles were used as a sensitive platform for the detection of Pb 2+ and Cd 2+ . Fe3 O4 with large specific surface area could increase the sensitivity for detection. PANI as a conductive polymer with excellent electronic conductivity not only improved the electron transport speed in the detection process, but also produced good chelation with heavy ions. PANI contains a large number of amino and imino groups on its surface, thereby improving the detection sensitivity. Under optimal experimental conditions, the linear range for the detection of Pb 2+ was from 0.1 to 10 4 nmol L −1 ; the detection limit was 0.03 nmol L −1, error limit of LOD was 1.1% and LOQ was 0.09 nmol L −1 . The calculated LOD value of Cd 2+ was 0.3 nmol L −1, the error limit of LOD was 1.5%, and LOQ was 0.9 nmol L −1 . The prepared electrochemical sensor presented high sensitivity, good specificity and excellent stability; also, it is simple and easy to operate. This analysis strategy has a huge application prospect in the detection of other heavy metal ions.